2005
DOI: 10.1111/j.1439-0418.2005.00981.x
|View full text |Cite
|
Sign up to set email alerts
|

Processed kaolin as an alternative insecticide against the European pear sucker, Cacopsylla pyri (L.)

Abstract: Application of processed kaolin particle film (Surround Ò WP; Engelhard Corporation, Iselin, NJ, USA) repels insects without lethal effects; hence side effects on beneficial arthropods are low. Processed kaolin may be an alternative to broad-spectrum insecticides used against European pear sucker, Cacopsylla pyri (L.), in organic and conventional pear production. A small-plot field trial was conducted in spring 2003 to assess this hypothesis. Multiple applications of processed kaolin during the first flying pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 13 publications
2
16
0
3
Order By: Relevance
“…Repellence from powder is likely, as particle Þlms, particularly those formed from kaolin, are known to be repellent to a range of insect pests (Daniel et al 2005) and widely used as barriers in pest control. It was, however, not possible to tell whether moths were making contact with powder before alighting, so the repellence may have been volatile related rather than physical avoidance.…”
Section: Discussionmentioning
confidence: 99%
“…Repellence from powder is likely, as particle Þlms, particularly those formed from kaolin, are known to be repellent to a range of insect pests (Daniel et al 2005) and widely used as barriers in pest control. It was, however, not possible to tell whether moths were making contact with powder before alighting, so the repellence may have been volatile related rather than physical avoidance.…”
Section: Discussionmentioning
confidence: 99%
“…Against D. abbreviatus , kaolin clay did not even exert a significant protection for treated leaf disks in choice tests. Other studies have observed successful suppression of arthropod pests on fruit plants coated with kaolin 3, 55, 56. According to these studies, a plant coated with a hydrophobic particle film barrier, such as kaolin clay, can repel arthropods not only by making the plant visually or tactilely unrecognizable as a potential host but also by restraining mobility and snaring the arthropod's mouthparts.…”
Section: Discussionmentioning
confidence: 99%
“…Kaolinin birçok bitkide zararlılara karşı da etkili olduğu belirlenmiştir. Armutlarda psillid [17], soğanlarda trips [18], pamukta pamuk kurdu [19], turunçgillerde Akdeniz meyve sineği [20], lahanada yaprakbiti [21] zararını azalttığı bildirilmektedir.…”
Section: Introductionunclassified